2019
DOI: 10.1186/s12903-019-0784-7
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, non-invasive tool for periodontitis screening in a medical care setting

Abstract: Background Since periodontitis is bi-directionally associated with several systemic diseases, such as diabetes mellitus and cardiovascular diseases, it is important for medical professionals in a non-dental setting to be able examine their patients for symptoms of periodontitis, and urge them to visit a dentist if necessary. However, they often lack the time, knowledge and resources to do so. We aim to develop and assess “quick and easy” screening tools for periodontitis, based on self-reported or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 44 publications
5
89
2
4
Order By: Relevance
“…Based on ROC statistics, in this study the predictive ability of a combination of questionnaire items and other sociodemographic and risk factors was comparable to other populations . Using the same classification, Eke and coworkers (2013) reported a ROC value of 0.81, while Heaton et al (2017) in a sample of African American women reported a ROC value of 0.79.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Based on ROC statistics, in this study the predictive ability of a combination of questionnaire items and other sociodemographic and risk factors was comparable to other populations . Using the same classification, Eke and coworkers (2013) reported a ROC value of 0.81, while Heaton et al (2017) in a sample of African American women reported a ROC value of 0.79.…”
Section: Discussionsupporting
confidence: 64%
“…Carra et al (2018) developed a periodontal screening score (PESS; calculated with five of the self‐reported items plus age and smoking) potentially useful to screen for severe periodontitis in a French population, showing a sensitivity of 78.9% and a specificity of 74.8%, with a ROC value of 0.82. Last, a recent study from the Netherlands evaluated the added value of using salivary biomarkers from oral rinse samples in addition to the questionnaire and demographic determinants, concluding that these may be redundant in periodontitis screening, as long as the questionnaire alone performed very well (ROC value of 0.78 for severe periodontitis) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*Estimated by applying screening tool. 28 a dentist, compared to 2.3±5.0 in those with a dentist (p=0.029). Patients without regular dentist consultation had a mean score of 3.7±7.0, compared to 2.1±4.6 in subjects who regularly visit a dentist (p=0.002) (Table S1).…”
Section: General Health-related Qolmentioning
confidence: 87%
“…tool. 28 This tool was able to accurately distinguish periodontitis patients, defined according to the golden standard, ie, full mouth clinical periodontal measurements. 29…”
Section: Self-reported Oral Health Measurementmentioning
confidence: 99%